If there be thorns - Andrews, V. C. (Virginia C.) (New York : Pocket Books, 1981)
Now a ballet teacher and mother of two boys, and married to the man no one else knows is her brother, Cathy begins to fear that she will be like her mother and make the horror of her childhood live again.
Sequel to: Petals on the wind.
Keywords: Mothers and daughters -- Fiction; Problem families -- Fiction; Revenge -- Fiction; Horror tales; Domestic fiction